PELAKSANAAN KUASA MENJUAL AGUNAN KREDIT PADA PT. BANK RAKYAT INDONESIA (PERSERO) TBK UNIT SUDIRMAN PEKANBARU - Setiawan, Dede; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The power of sale that is made by the parties jointly is basically only in the form of formalitiesbecause, collateral for loans guaranteed to the Bank has been tied to mortgage rights by conducting anauction as a form of repayment of debt. The purpose of this thesis is: First, To find out the inclusion of thepower of selling clause in the credit agreement at PT. Bank Rakyat Indonesia (Persero) Tbk PekanbaruSudirman Unit is in accordance with applicable rules. Second, to find out what factors cause the power tosell credit collateral received by PT. Bank Rakyat Indonesia (Persero) Unit Sudirman Pekanbaru in thepractice of granting credit.This type of research is sociological juridical research which means reviewing the state of the problemin the field associated with applicable legal aspects and regulating the problem, while the nature of theresearch is descriptive, where descriptive research describes clearly and in detail the implementation ofcredit collateral at PT. . Bank Rakyat Indonesia (Persero) Tbk Sudirman Unit Pekanbaru.From the results of the study concluded, Inclusion of the power of selling clause on credit agreementsat PT. The Bank Rakyat Indonesia (Persero) Tbk Pekanbaru Sudirman Unit is that it has been carried outaccording to the provisions but still causes losses to the debtor even though the power selling clause is madeto provide benefits to the parties but this has not been felt by the debtor because the Bank has unilaterallydetermined the selling price from collateral goods in the process of selling collateral goods due to baddebtor customers' credit Even though in the power of attorney there is also the power to set prices by theauthorized recipient (creditor), but the power of attorney is not entitled to set a price so low that the powerof attorney, and Factor factors that cause the power to sell the credit collateral received by PT. Bank RakyatIndonesia (Persero) Unit Sudirman Pekanbaru in the practice of granting credit is minimizing auctions dueto bad credit, Avoiding auction taxes at 10% of the value of transactions, carrying out sales of assets againstbad credit that the income from the sale is immediately put into bank finances because the People's BankIndonesia and the power to sell it are very effective, easier, the cost is cheap and not complicated if theobject of collateral will be sold when the debtor defaults / defaults.Keywords : Power Implementation - Selling Collateral – Credit